2014
DOI: 10.1186/cc13790
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and its association with season, hospital and sepsis mortality in critical illness

Abstract: IntroductionVitamin D plays a key role in immune function. Deficiency may aggravate the incidence and outcome of infectious complications in critically ill patients. We aimed to evaluate the prevalence of vitamin D deficiency and the correlation between serum 25-hydroxyvitamin D (25(OH) D) and hospital mortality, sepsis mortality and blood culture positivity.MethodsIn a single-center retrospective observational study at a tertiary care center in Graz, Austria, 655 surgical and nonsurgical critically ill patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
129
6
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 59 publications
7
129
6
9
Order By: Relevance
“…We observed a higher incidence of 25 (OH) D deficiency in critically ill patients than previously reported (10)(11)(12)(13)(14)(15)(16)(17)(23)(24)(25). However, most of these studies were from developed countries.…”
Section: Discussioncontrasting
confidence: 59%
“…We observed a higher incidence of 25 (OH) D deficiency in critically ill patients than previously reported (10)(11)(12)(13)(14)(15)(16)(17)(23)(24)(25). However, most of these studies were from developed countries.…”
Section: Discussioncontrasting
confidence: 59%
“…This may result in even lower ''vitamin D levels'' as serum 25(OH)D is the accepted marker for vitamin D status. Several studies report low vitamin D levels to be a biomarker associated with sepsis severity, organ dysfunction and even mortality in critically ill patients (18)(19)(20)(21)(22)(23)(24).…”
Section: Vitamin D Deficiency In the Critically Illmentioning
confidence: 99%
“…The findings, reported by Amrein and colleagues [32], have revealed that the vast majority (87%) of ICU patients had low or very low concentrations of vitamin D, which was positively correlated with mortality. The study carried out by Venkatram and colleagues [33] demonstrated a correlation between the concentration of 25(OH)D in patients in a multi-specialized ICU and hospital mortality.…”
Section: Significance Of Vitamin D In Icu Patientsmentioning
confidence: 93%